Changes in Lipid Profile Secondary to Asymptomatic Malaria in Migrants from Sub-Saharan Africa: A Retrospective Analysis of a 2010–2022 Cohort - Diego Gayoso-Cantero; María Dolores Corbacho-Loarte; Clara Crespillo-Andújar; Sandra Chamorro-Tojeiro; Francesca Norman; Jose A. Perez-Molina; Marta González-Sanz; Oihane Martín; José Miguel Rubio; Beatriz Gullón-Peña; Laura del Campo Albendea; Rogelio López-Vélez; et al. (Tropical Medicine and Infectious Disease)
Altered lipid profiles have been observed in acute malaria, though mechanisms remain unclear. The impact of asymptomatic submicroscopic malaria infection (AMI) on lipids is unexploredAn observational, comparative, retrospective study was conducted of 1278 asymptomatic Sub-Saharan African migrants (ASSAMs) screened for malaria and lipid profiles during health exams (2010–2022). A systematic screening protocol for infectious disease was performed, including screening for Plasmodium spp. infection by polymerase chain reaction (PCR).Among 800 ASSAMs screened for malaria, 104 (13%) were PCR-positive: P. falciparum (68.72%), P. malariae (18.27%), P. ovale (9.62%), and mixed infections (3.8%). Participants with AMIs exhibited lower baseline lipid levels: total cholesterol (146 vs. 163 mg/dL; p < 0.001), HDL (43 vs. 47 mg/dL; p < 0.001), and LDL (87.5 vs. 98 mg/dL; p < 0.001), with no differences in triglycerides. After treatment, lipid levels partially equalized: total cholesterol (156 vs. 166; p = 0.01), HDL (44 vs. 47.5; p = 0.05), LDL (102 vs. 108.5; p = 0.31), with no changes in triglycerides. Patients with AMI showed higher rates of co-infections (Strongyloides 20.61% vs. 14.35%; p < 0.001; filariae 7.69% vs. 1.91%; p = 0.02) and lower mean corpuscular volume (87.2 vs. 85; p < 0.001). Conclusions: These findings suggest that cholesterol reductions in AMI are not solely due to acute inflammation but may reflect chronic inflammatory processes triggered by asymptomatic malaria. This supports a potential link between AMI and lipid profile changes, underscoring its role in subclinical chronic inflammation.